Functionalized Carbon Nanoparticles, Blacks and Soots as Electron‐Transfer Building Blocks and Conduits. Issue 5 (11th March 2014) - Lawrence, Katherine; Baker, Charlotte L.; James, Tony D.; Bull, Steven D.; Lawrence, Ruth; Mitchels, John M.; Opallo, Marcin; Arotiba, Omotayo A.; Ozoemena, Kenneth I.; Marken, Frank
Abstract Functionalized carbon nanoparticles (or blacks) have promise as novel active high‐surface‐area electrode materials, as conduits for electrons to enzymes or connections through lipid films, or as nano‐building blocks in electroanalysis. With previous applications of bare nanoblacks and composites mainly in electrochemical charge storage and as substrates in fuel cell devices, the full range of benefits of bare and functionalized carbon nanoparticles in assemblies and composite (bio)electrodes is still emerging. Carbon nanoparticles are readily surface‐modified, functionalized, embedded, or assembled into nanostructures, employed in bioelectrochemical systems, and incorporated into novel electrochemical sensing devices. This focus review summarizes aspects of a rapidly growing field and some of the recent developments in carbon nanoparticle functionalization with potential applications in (bio)electrochemical, photoelectrochemical, and electroanalytical processes.